PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 016 SIMPANG POROS KECAMATAN RIMBA MELINTANG - Sri Mulyanti Mulyanti; Zariul Antosa Antosa; Damanhuri Daud Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The study design was a classroom action research (CAR). research was conducted in two cycles of four meetings and two replications of material daily. background of the problem in this study is the low student learning outcomes fourth grade intersections shaft 016 countries with an average value of 69.5% of 20 students reached the KKM beelom as many as 13 people (65%). KKM while reaching only 7 people (70%). formulation of the problem in this research "is research cooperative learning model Numbered Heads Together (NHT) can improve the learning outcomes of students social studies student learning outcomes through the implementation of IPS cooperatif learning model types Numbered Heads Together (NHT) class IV 016 public primary axis intersection. The experiment was conducted in the second semester of the school year in March 2014 2013/2014 subjects were fourth grade students of SD Negeri Simpang shaft 016 by the number of students 20 people, consisting of 11 boys and 9 girls. Data collection instrument in this study is the observation sheet and the teacher and the student achievement test. Once implemented cooperative learning model Numbered Heads Together (NHT). Based on these results it can be concluded that the application of cooperative learning model Numbered Heads Together (NHT) can improve student learning outcomes fourth grade public school districts 016 spindle Simpang Rimba Rokan Hilir Transversefourth grade Simpang 016 shaft country?". purpose of this study to improve. Keywords: Cooperative learning model typeNumbered Heads Together (NHT) development of  communication technology,learning outcomes ips.